Combination therapy with alemtuzumab: existing data and future studies (Hematology Meeting Reports, 2009)
Chronic lymphocytic leukaemia (CLL) is the most common form of leukaemia in the western world. CLL is generally considered an indolent disease affecting older patients greater than 60 years of age, but a significant proportion of patients diagnosed with CLL are less than 55 years old, or present with an aggressive and resistant form of CLL that is associated with serious infectious and autoimmune complications. Traditional first-line therapy for CLL utilises alkylating agents such as chlorambucil. In more recent years the antimetabolite fludarabine has been investigated in randomized clinical trials, producing notable results such as increased rates of overall response, complete response (CR) and progression-free survival. However, improved overall survival has not been observed in clinical trials. Patients who have achieved an apparent CR according to National Cancer Institute Working Group (NCI-WG) criteria might still have minimal residual disease (MRD). From these residual leukaemic cells, new disease can arise, leading to relapse and shortening of progression-free survival and overall survival. Recent development of highly sensitive techniques able to detect the presence of MRD at levels previously undetectable has meant that the potential for the complete eradication of MRD exists. In an attempt to capitalise on the promising results obtained with fludarabine, and to increase survival of patients with CLL, novel fludarabine combination therapies are now being used. Combinations of fludarabine with alkylating agents, anthracyclines and monoclonal antibodies have been shown to increase antitumour effects in clinical studies, both in previously untreated patients and in patients refractory to previous therapies, including fludarabine monotherapy. Specifically, combinations of fludarabine with the monoclonal antibody alemtuzumab have increased the complete and partial response rates in patients with CLL irrespective of their treatment history, and similar results have been obtained in other fludarabine-based antibody-chemotherapy combinations. These encouraging results have led to the design of several ongoing phase III trials of fludarabine combination therapy; the results of these studies will likely lead to improved strategies for individualised treatment of patients with CLL, prolonging overall survival and potentially leading to cure.